Production of Some Shallots Varieties at Different Plant Spacing - Zulfahmi, Reza; Lestari, Mustika Adzania; Sari, Hevia Purnama; Putrantri, Desty Aulia (Akta Agrosia, 2023)
The demand for shallots continues to rise annually, yet production fails to meet the growing need. Enhancing production through strategic plant spacing and the utilization of diverse shallot varieties is imperative. This research aims to determine the optimal plant spacing for shallots and evaluate the performance of different shallot varieties under varying planting distances. A factorial Randomized Complete Block Design (RCBD) with two factors was employed, investigating three shallot types (Bima Brebes, Maja Cipanas, and Tajuk) and testing three planting distances (15 cm x 15 cm, 20 cm x 20 cm, and 25 cm x 25 cm). Each treatment was replicated four times, and data were collected on various parameters including leaf length, leaf diameter, number of leaves, bulb length, bulb diameter, number of tillers, bulb fresh weight, bulb dry weight, bulb weight per cluster, and bulb dry weight per cluster. Results indicate that Bima Brebes and Maja  memahami pentingnya dukungan pelanggan yang responsif. Oleh karena itu, mereka menyediakan layanan pelanggan yang siap membantu pemain kapan saja Cipanas types demonstrated the highest bulb dry weight per cluster, with 32.69 grams and 31.71 grams, respectively. The optimal plant spacing identified is 20 cm x 20 cm, promoting increased leaf and bulb diameter, as well as enhanced bulb dry weight per cluster. Keywords: plant spacing, shallot, variety testing, yield,